Pengaruh Kompetensi Guru Berdasarkan 2 Timotius 2:2 terhadap Efektivitas Pembelajaran di SMP Distrik Ransiki, Manokwari Selatan - Esty Rahayu; Timotius Sukarna; Terifena Lontoh (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
This study examines the relationship between teacher competence based on 2 Timothy 2:2 and learning effectiveness in junior high schools in Ransiki District, South Manokwari. This research uses quantitative method with data collection through questionnaires filled out by 49 teachers. The results showed a significant correlation between teacher competence and learning effectiveness (r = 0.713, p < 0.05). Teacher competence, especially in the use of technology, plays an important role in improving the effectiveness of the learning process. This research confirms the importance of teachers' moral values and professionalism in improving the quality of education.